Exploring Shariah Governance Practices in Islamic Co-Operatives in Malaysia - Kamaruddin, Muhammad Iqmal Hisham; Salleh, Supiah; Shafii, Zurina; Hanefah, Mustafa Mohd; Zakaria, Nurazalia (International Journal of Economics and Financial Issues, 2024)
This study aims to explore the current Shariah governance practices, Shariah function practices and Shariah governance issues and challenges in Islamic co-operatives in Malaysia. For this, a physical town hall session with 64 representatives from 39 Islamic co-operatives was conducted for data collection. The empirical finding indicates that the Shariah Advisory Council (SAC) of the Malaysia Co-operative Societies Commission (SKM) was perceived to play similar roles like the Shariah Advisory Council (SAC) of the Bank Negara Malaysia (BNM) and the Securities Commission of Malaysia (SC). Besides, management of Islamic co-operatives in Malaysia also see the need to create a Shariah committee at the co-operative level as part of good Shariah governance practices. Moreover, although more than half of the respondents admit that their respective co-operatives are already implementing Shariah governance practices, the implementation of Shariah function such as Shariah review and Shariah audit is still at the initial stage, with more than half of Islamic co-operatives yet to implement this Shariah function. In addition, several issues and challenges have been identified in the implementation of Shariah governance in Islamic co-operatives. This study is expected to contribute to enhancing Shariah governance practices in Islamic co-operatives to ensure better Shariah compliance.